Theorizing the Golden Age Musical: Genre, Structure, Syntax - Kim H. Kowalke (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2014)
In 1956 Leonard Bernstein opined to his Omnibus audience that “the American musical theater has come a long way, borrowing this from opera, that from revue, the other from operetta, something else from vaudeville—and mixing all the elements into something quite new.” Although he suggested that “each [new musical] is a surprise; nobody ever knows what new twists and treatments and styles will appear next,” at this midpoint in the Golden Age of the American musical theater (roughly the quarter century between Oklahoma! [1943] and Hair [1968]), the art form had evolved its own elaborate set of generic expectations, structural and syntactical norms, and stylistic conventions. As the various subgenres (musical play, musical comedy, Broadway opera) gradually coalesced under the all-encompassing umbrella term of “musical,” the classic musicals of the Golden Age collectively defined an elaborate “code of conduct” that allowed its creative collaborators to explore new ways of integrating music, drama, dance, and spectacle within the overtly commercial arena of the Broadway theater, wherein audience response functioned as the final critical arbiter. During its Golden Age, the American musical theater came of age, and in so doing became the representative international musico-dramatic genre of the twentieth century. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part V).